Running-In Behavior and Failure Mechanism Between AgCuNi Alloy and Au-Electroplated Layer - Hongjian Wu; Ya’nan Zhang; Qingjian Jia; Hui Cao; Han Li; Ming Ma (Sensors)
To avoid wear and tear of the slip ring due to electrical corrosion, the slip ring needs to undergo the running-in process under atmospheric conditions without current after assembly. To address the urgent demand for long-service capability space conductive slip rings in the aerospace field, the running-in behavior and failure mechanism between the AgCuNi alloy and Au-electroplated layer are investigated using a ball-on-disc tribometer in this paper. The results show that the transfer film composed of Au plays an important role in modifying the friction during the sliding process. With the accumulation of wear debris composed of Ag on the disc, the contact material of the friction pair changed from Au and Au to Au, Ag and Au, so the surface roughness of wear tracks increased. Finally, the transfer film broke, which made the layer fail. This paper reveals the key element failure mechanism that causes transfer film failure in the running-in contact area, which is used to reveal the friction behavior and failure mechanism of slip ring friction pair materials, and provides a basis for the selection of running-in parameters during the running-in process of slip rings before power-on operation.